2022
DOI: 10.1007/s00394-022-02805-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary B group vitamin intake and the bladder cancer risk: a pooled analysis of prospective cohort studies

Abstract: Purpose Diet may play an essential role in the aetiology of bladder cancer (BC). The B group complex vitamins involve diverse biological functions that could be influential in cancer prevention. The aim of the present study was to investigate the association between various components of the B group vitamin complex and BC risk. Methods Dietary data were pooled from four cohort studies. Food item intake was converted to daily intakes of B group vitamins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…2 Adjusted for age at cohort entry, race and ethnicity, and total energy intake. 3 Further adjusted for family history of bladder cancer, employment in a high-risk industry, smoking status, average number of cigarettes, squared average number of cigarettes, number of years smoked (time-dependent), number of years since quitting (time-dependent), interactions of race/ethnicity with smoking status, average number of cigarettes, squared average number of cigarettes, and number of years smoked. HEI-2015 and DASH were additionally adjusted for alcohol intake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Adjusted for age at cohort entry, race and ethnicity, and total energy intake. 3 Further adjusted for family history of bladder cancer, employment in a high-risk industry, smoking status, average number of cigarettes, squared average number of cigarettes, number of years smoked (time-dependent), number of years since quitting (time-dependent), interactions of race/ethnicity with smoking status, average number of cigarettes, squared average number of cigarettes, and number of years smoked. HEI-2015 and DASH were additionally adjusted for alcohol intake.…”
Section: Resultsmentioning
confidence: 99%
“…The QFFQ included more than 180 food items and was validated through a calibration study, which showed satisfactory correlations (0.57-0.74) for nutrient densities compared to three 24 h dietary recalls [12]. Within the framework of the Dietary Patterns Methods Project, four pre-defined diet quality indices were computed: (1) the Healthy Eating Index-2015 (HEI-2015), (2) the Alternative Healthy Eating Index-2010 (AHEI-2010), (3) the alternate Mediterranean diet (aMED), and (4) Dietary Approaches to Stop Hypertension (DASH) scores [13][14][15]. HEI-2015, a comprehensive scoring system with a potential score range of 0 to 100 points, encompasses 13 components, evaluating adherence to the Dietary Guidelines for Americans 2015-2020 [16].…”
Section: Diet Quality Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on vitamin B12 intake from foods, or foods and supplements, were less consistent than those on blood concentrations. Additionally, low B12 intake has also been shown to be associated with cancer [ 61 , 62 ]. Studies collecting nutritional intake data in the past years are subject to recall bias and are not a reliable source of evidence on causality.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the proven ability of calcium to protect against the formation of cancer, the occurrence of hypocalcemia might play a role in the initiation of BC. Nevertheless, despite the presumed safeguarding benefits of vitamin D, the investigation carried out by Boot et al No significant inverse correlation was found between the intake of vitamin D through diet and the risk of BC [88]. The hypothesized protective effect of vitamin D could not be confirmed in a meta-analysis conducted by Chen et al as well, which specifically examined the role of vitamin D intake from both diet and supplements [86].…”
Section: Effects Of Nutrients On Bladder Cancer Progressionmentioning
confidence: 97%